2017
DOI: 10.1371/journal.pone.0170550
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of Influenza Vaccination Intention and Behavior – A Systematic Review of Influenza Vaccine Hesitancy, 2005 – 2016

Abstract: BackgroundInfluenza vaccine hesitancy is a significant threat to global efforts to reduce the burden of seasonal and pandemic influenza. Potential barriers of influenza vaccination need to be identified to inform interventions to raise awareness, influenza vaccine acceptance and uptake.ObjectiveThis review aims to (1) identify relevant studies and extract individual barriers of seasonal and pandemic influenza vaccination for risk groups and the general public; and (2) map knowledge gaps in understanding influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

92
887
9
24

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 927 publications
(1,072 citation statements)
references
References 415 publications
92
887
9
24
Order By: Relevance
“…34,35 Evaluations of programs targeting nurses suggest that multipronged approaches are necessary [36][37][38][39] to address the myriad reasons for vaccine hesitancy and refusal in this occupational group. 24,40 Lastly, in our study population, people identifying as Black had lower odds of being vaccinated against influenza compared with those with European heritage. Earlier findings of ethnicity's association with vaccine uptake have been contradictory.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…34,35 Evaluations of programs targeting nurses suggest that multipronged approaches are necessary [36][37][38][39] to address the myriad reasons for vaccine hesitancy and refusal in this occupational group. 24,40 Lastly, in our study population, people identifying as Black had lower odds of being vaccinated against influenza compared with those with European heritage. Earlier findings of ethnicity's association with vaccine uptake have been contradictory.…”
Section: Discussionmentioning
confidence: 62%
“…It is likely necessary to tailor immunization programs differently to reach HCW at all levels of uptake, from refusers to those accepting influenza vaccine intermittently to those vaccinated annually. Reviews of the literature report that believing that influenza vaccine is effective, that influenza is highly contagious, and that prevention is important (including HCWs’ roles in transmission) are predictive of influenza vaccination . Further research is needed to determine how common concerns related to vaccine hesitancy in HCW (e.g vaccine safety and efficacy, perceived low risk of illness) are associated with the frequency of vaccine uptake in HCW working in settings with different vaccination policies and work cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reasons for receiving and not receiving vaccination have been identified in the literatures. For example, studies have shown that the common reasons for not receiving vaccination among nurses included low levels of risk perception, concerns about side effects, questions about vaccine's effectiveness/safety, inconvenience in accessing vaccination, fear of pain, or negative reports from media (Ajenjo et al, 2010;Clark, Cowan, & Wortley, 2009;Corace et al, 2013;Giannattasio et al, 2015;Hollmeyer, Hayden, Poland, & Buchholz, 2009;Maltezou et al, 2008;Schmid, Rauber, Betsch, Lidolt, & Denker, 2017;Wang, Lee, & Lee, 2015;Weingarten, Riedinger, Bolton, Miles, & Ault, 1989;Zhang, While, & Norman, 2011). On the other hand, the reasons for receiving vaccination among nurses included protecting oneself, patient, family members, friends and children, to avoid sick leave, recommendation/mandate by employer, perception of vaccine's effectiveness/ safety and accessibility of vaccination (Haviari et al, 2015;Hollmeyer et al, 2009;Maltezou et al, 2008;Tosh, Jacobson, & Poland, 2010;Zhang et al, 2011).…”
Section: Determinants Of Getting Influenza Vaccinationmentioning
confidence: 99%
“…Lastly, vaccine hesitancy among parents could contribute to this finding, although this was not explored in this outreach program. A systematic review on vaccine hesitancy identified that the lack of recommendations from medical personnel to parents for children to receive vaccine, the lack of perceived benefit of vaccine by the parents, and inconvenience to receive vaccine have contributed to vaccine hesitancy among parents 24 . In future outreach programs, the strategies that could be explored to optimise delivery to this population include targeting sites where children under five years of age frequently attend (such as the maternal child health clinics), and providing education to parents about the availability and benefit of the vaccines to children of this age group.…”
Section: Discussionmentioning
confidence: 99%